DECLINE RATE TRANSIENT ANALYSIS USING MATERIAL BALANCE TIME IN NATURALLY FRACTURED RESERVOIR - Feni Maulindani, Sri
A naturally fractured reservoir is a unique reservoir because has two continuums: they are matrix and fractures, where the mechanism is different from the conventional reservoir. The biggest contribution of production fluid flow from this reservoir is through the interconnected fractures network, where the fluid storage in the matrix flows to the wellbore more through those networks (this is the so-called dual porosity system). Therefore the behavior of this reservoir is not the same as a commonly conventional homogenous reservoir (single porosity system). The rate transient and Decline Curve analysis for this dual-porosity reservoir cannot use the decline curve method that is commonly used for the homogenous reservoir. This research developed the Type Curve for Decline Rate Transient analysis using the Material Balance Time method for a dual-porosity system, to be used for estimating reserve and characterizing the naturally fractured reservoir behavior. This research followed and modified mathematical model that has been developed by the previous researcher in the Laplace domain and found a solution using the Gaver-Stehfest Algorithm, involving various parameters that influence the naturally fractured reservoir behavior such: Storativity Ratio or Omega is the storage capacity of fluid in fracture, Interporosity Flow Coefficient or Lamda is the ability of a fluid to flow from the matrix to the fracture, drainage radius, and fluid flow from the matrix into the fracture network (in both fashions of pseudo -steady-state and transient inter-porosity flow models). vi The resulted Type Curve is then validated with the synthetic model using a commercial simulator. Two shape factors that were considered, are Warren and Root model (Pseudosteady state flow) and Kazemi and Gilman model (Transient interporosity flow). Both are constrained by a constant well production rate. Those proposed Type Curves are then applied using the data from the published paper (Da Prat, et all) and give a considerably good match. And also those proposed Type Curves are then applied using the data from Jatibarang Field and give a considerably good match